What is happening in extension and social outreach (VITAL, 2025)
Training courses were held on maternal health, care for victims of sexual abuse, medical emergencies, strengthening the immune system, etc. Health brigades and a specialized course on vertical childbirth care were carried out.
Keywords: Maternal health; Vertical childbirth; Medical emergencies; Immune system; Health brigades